Apakah Ekuitas Merek dan Kesadaran Halal Memediasi Pengaruh Religiusitas dan Akulturasi terhadap Keputusan Pembelian? - Dwi Ratna Sari; Asep Maulana Rohimat; Zulfikar Ali Ahmad (JESI (Jurnal Ekonomi Syariah Indonesia), 2021)
When the Korean Wave became a new trend in Indonesia, many Indonesian Muslims were influenced by the Korean culinary culture. Many people do not pay attention to the halal aspects of food, especially Korean food where the majority of the population is non-Muslim. From this the researchers conducted research on the effect of religiosity and acculturation on halal decisions with brand equity and halal awareness as mediating variables. This study uses a convenience sampling method with Korean food consumer object samples taken as many as 97 respondents randomly. Data analysis techniques used are multiple linear regression tests and multiple tests. The results of the study show that religiosity has a significant effect on brand equity, acculturation has a significant effect on brand equity, religiosity has a significant effect on halal awareness, but acculturation has a not significant effect on halal awareness, religiosity and acculturation has a significant effect on purchasing decisions, brand equity has an effect on significant on purchasing decisions and halal awareness has a significant effect on purchasing decisions. Brand equity mediates the effect of religiosity and acculturation on purchasing decisions. Meanwhile, halal awareness mediates the influence of religiosity on purchasing decisions.